Social determinants of gastrointestinal malformation mortality in Brazil: a national study - David P Mooney; Fabio Botelho; Gabriella Hyman; Joaquim Bustorff-Silva; Amanda Rosendo; Ayla Gerk; Julia Ferreira; Luiza Telles; Arícia Gomes Miranda; Madeleine Carroll; Bruna Oliveira Trindade; Sarah Bueno Motter; et al. (BMJ Publishing Group, 2024)
Introduction In Brazil, approximately 5% are born with a congenital disorder, potentially fatal without surgery. This study aims to evaluate the relationship between gastrointestinal congenital malformation (GICM) mortality, health indicators, and socioeconomic factors in Brazil.Methods GICM admissions (Q39-Q45) between 2012 and 2019 were collected using national databases. Patient demographics, socioeconomic factors, clinical management, outcomes, and the healthcare workforce density were also accounted for. Pediatric Surgical Workforce density and the number of neonatal intensive care units in a region were extracted from national datasets and combined to create a clinical index termed 'NeoSurg'. Socioeconomic variables were combined to create a socioeconomic index termed 'SocEcon'. Simple linear regression was used to investigate if the temporal changes of both indexes were significant. The correlation between mortality and the different indicators in Brazil was evaluated using Pearson's correlation coefficient.Results Over 8 years, Brazil recorded 12804 GICM admissions. The Southeast led with 6147 cases, followed by the Northeast (2660), South (1727), North (1427), and Midwest (843). The North and Northeast reported the highest mortality, lowest NeoSurg, and SocEcon Index rates. Nevertheless, mortality rates declined across regions from 7.7% (2012) to 3.9% (2019), a 51.7% drop. The North and Midwest experienced the most substantial reductions, at 63% and 75%, respectively. Mortality significantly correlated with the indexes in nearly all regions (p<0.05).Conclusion Our study highlights the correlation between social determinants of health and GICM mortality in Brazil, using two novel indexes in the pediatric population. These findings provide an opportunity to rethink and discuss new indicators that could enhance our understanding of our country and could lead to the development of necessary solutions to tackle existing challenges in Brazil and globally.